The Effectiveness of the Karamunting Genzi Parenting Monitoring Card Model for Undernourished Children Receiving Local-Based Supplementary Feeding - Zenderi Wardani; Ori Pertami Enardi; Ratmawati (Citra Delima Scientific journal of Citra Internasional Institute, 2025)
The reduction in wasting prevalence in Pangkalpinang City from 5.1% in 2021 to 4.9% in 2022 was statistically insignificant, reflecting a marginal decline of only 0.2%, still near the threshold.Pangkal Balam Health Center allocated the highest budget to serve 59 undernourished children under five. This study aimed to evaluate the implementation of a nutrition education model using the "Karamunting Genzi" Parenting Monitoring Card, an educational and self-assessment tool designed to support mothers and caregivers in planning and evaluating age-appropriate feeding practices. This study uses a quasi-experimental design with a cross-sectional approach. Respondents consist of 44 mothers/caregivers of U-5 children undernourished and receiving locally based supplementary feeding (PMT). The interventions consisted of cadre training, home visits, and using the Karamunting Genzi Monitoring Card as a monitoring tool. Data was collected using structured questionnaires and analyzed using  Spearman's rank tests. The intervention engaged 10 community health (Posyandu) cadres to support 44 participating mothers across five urban villages, focusing on improving feeding knowledge and practices. Post-intervention assessments showed significant improvements in maternal knowledge (mean score increased from 65.9 to 67.6) and feeding practices (94.1 to 96.2). Spearman's rank test showed a strong relationship between pre- and post-intervention knowledge scores (rs = 0.775) and parenting practices (rs = 0.766). This study recommends replicating intervention in other areas, conducting long-term behavioral monitoring, developing more interactive educational media, and integrating the tool into broader nutrition programs through collaboration with the government and relevant stakeholders to address childhood malnutrition effectively.